The Collected Works of Aron Gurwitsch (1901-1973) - Gurwitsch, Aron. author. aut Link
XXVI, 521 p.
Keywords: The second of a planned six volume of Gurwitsch’s writings, this volume is a corrected version of a collection he published in 1966. It was intended to complement the English edition of The Field of Consciousness (1964), which is the third volume of these Works in English. It contains his own introduction addressing his motivation as a phenomenologist and the situation at the time of publication. Included are English translations of his doctoral thesis, Phenomenology of Thematics and the Pure Ego (1929) and the substantial study based on his first Sorbonne lecture course, "Some Aspects and Developments of Gestalt Psychology" (1936), which made his name in Paris when he fled there from Germany after the rise of National Socialism. Other studies draw on the work in psychiatry of Kurt Goldstein and relate phenomenology to René Descartes, William James, Immanuel Kant, and tendencies in modern thought, thus complementing the historical perspectives resorted of in Vol. I. Thematic problematics addressed include the noema, the ego, eideation, and logic.